2022
DOI: 10.1002/er.7687
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of structural stability of cathode by manganese additive in electrolyte for zinc‐ion batteries

Abstract: Summary Zinc‐ion batteries (ZIBs) are considered a candidate for lithium‐ion batteries owing to their low cost, eco‐friendly nature, and high safety level. In particular, their energy density is high because of a two‐electron transfer mechanism involving Zn ions. However, ZIBs have the demerits of low‐rate capability and poor cycling life because of the dissolution of Mn in the electrolyte during charging and discharging, which prevents the high potential of ZIBs from being effectively utilized. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Various additives can effectively address challenges in batteries, such as improving electrode surface morphology and/or reducing dendrite growth by lowering electrolyte reactivity, enhancing electrolyte stability, and/or minimizing the formation of passivation layers to reduce capacity degradation. [83][84][85][86] These challenges also exist in Zn-S batteries, hindering their largescale deployment. Recent research has shown that incorporating electrolyte additives with redox regulation capabilities is a promising strategy for improving the performance of zincsulfur batteries due to their simple preparation process and effectiveness.…”
Section: Additive Engineeringmentioning
confidence: 99%
“…Various additives can effectively address challenges in batteries, such as improving electrode surface morphology and/or reducing dendrite growth by lowering electrolyte reactivity, enhancing electrolyte stability, and/or minimizing the formation of passivation layers to reduce capacity degradation. [83][84][85][86] These challenges also exist in Zn-S batteries, hindering their largescale deployment. Recent research has shown that incorporating electrolyte additives with redox regulation capabilities is a promising strategy for improving the performance of zincsulfur batteries due to their simple preparation process and effectiveness.…”
Section: Additive Engineeringmentioning
confidence: 99%
“…have not been studied in a low-temperature environment. At the same time, because the ion transport rate is seriously slowed in the low-temperature system, for the cathodic material with a loose structure (such as MnO 2 ), after the cation is dissolved, it cannot return to the original lattice structure, which has an irreversible effect on the capacity. , Therefore, it is attractive and challenging to design a low-temperature and high-performance vanadate-based AZIB system.…”
Section: Introductionmentioning
confidence: 99%
“…However, the MnO 2 cathode will undergo severe structural degradation during the cycle, resulting in a decrease in the cycle performance. Several optimization strategies, such as structural design, 31 cationic doping, 32 carbon coating, and electrolyte additive, 33 have been reported to enhance the electrochemical performance of manganese oxides. Cationic doping, as a common strategy for structural modification, has been proven to be effective in improving the electrochemical performance.…”
Section: ■ Introductionmentioning
confidence: 99%